ChemInform Abstract: Advanced Biotechnology: Metabolically Engineered Cells for the Bio‐Based Production of Chemicals and Fuels, Materials, and Health‐Care Products. Issue 18 (May 2015) - Becker, Judith; Wittmann, Christoph
Abstract Review: [184 refs.